PENYELESAIAN SISTEM PERSAMAAN LINEAR KOMPLEKS MENGGUNAKAN DEKOMPOSISI LU - Adam - Sopiyandi (Nurjati Journal of Mathematics and Mathematical Sciences (NJMMS), 2021)
In real cases, a system of linear equations is often applied to various kinds of problems, with the development of this theory also the development of new methods to determine more effective solutions. usually another form of a system of linear equations is denoted as Ax=b. In addition, the work of this study aims to in addition to fostering curiosity and to find solutions for solving complex number linear equation systems using LU Decomposition can also assist future researchers in solving problems that have similar topics. The method that will be applied is in the form of a literature study with a view to strengthening the discussion in the future. In addition, the discussion of the study taken will only focus on complex numbers spl. And with this study, it is hoped that it will be useful, whether it is adding insight or adding new, more creative researchers regarding the discussion of SPL using other methods, especially in complex numbers.